Protective Influence of Ficus asperifolia Miq Leaf Extract on Carbon tetrachloride (CCL4)-Induced Testicular Toxicity in rat’s Testes - Oluwafemi Adeleke Ojo, Adebola Busola Ojo, Bashir Ajiboye, Adewale Fadaka, Oluwatosin Debbie Imiere, Oluwatosin Adeyonu, Isreal Olayide (Journal of Applied Pharmaceutical Science, 2016)
The aim of this study was to investigate the ability of the polyphenolic rich Ficus asperifolia (Miq.) leaf extract in protecting rat testes against carbon tetrachloride-induced testicular damage in male Wistar rats. Thirty rats (weighing 140 - 180 g) were divided into five groups. In each treatment groups, aqueous extract of F. asperifolia (100, 200 and 400 mg/kg bw) administered by oral gavage for 21 days before exposure to carbon tetrachloride (CCl4) 3 mL kg 1i.p. were used to test protective influence of the plant extract. Protective influence were observed on antioxidant marker enzymes such as reduced glutathione (GSH) levels, catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD), and malonaldehyde (MDA) and histological examination. Animal exposure to the CCl4 resulted in significant elevation in the MDA with concomitant depletion (p < 0.05) in the level of GPx, CAT and SOD activities compared with control. Daily oral administration of F. asperifolia showed beneficial and ameliorative effects in all biochemical parameter evaluated. Histopathological alteration in testes was observed in CCl4 untreated rats and was ameliorated inCCl4 rats treated with F. asperifolia. Result shows that the aqueous leaf extract of F. Asperifolia has ameliorative effect against carbontetrachloride-induced testicular toxicity.
Keywords: Ficus asperifolia, Testes, Antioxidant, Histopathological changes, Carbon tetrachloride.